ALAT PELINDUNG TELINGA (EAR MUFF) DALAM MEREDUKSI TEKANAN DARAH TENAGA KERJA TERPAPAR KEBISINGAN: (Studi Kasus Pada Pekerja di Home Industri Terasi Palang Tuban) - Ernita Sari; Demes Nurmayanti; Faizatul Ummah (Poltekkes Kemenkes Surabaya, 2022)
Noise is the presence of unwanted loud noises by workers that can be harmful and cause emotional stress and affect hormone production, resulting in increased blood pressure. Increased blood pressure can be reduced by wearing ear protection for workers who are exposed to noise. This study aims to analyze the use of ear protective equipment in an effort to reduce the blood pressure of workers who are exposed to noise. The method used in this research is a field experiment with the same subject (labor) as the unit of analysis, namely the process of comparing the blood pressure of workers before and after work and wearing ear protection. This study used Wilcoxon to analyze the difference in the blood pressure of workers before and after wearing ear protection, and the chi-square test was used with the aim of seing the effect of labor characteristics on increasing blood pressure. The results of this study showed changes in blood pressure, these changes can be seen by the difference between blood pressure before work and after work by wearing ear protection with a value of p= 0,000. and the results of the chi-square test obtained a value of p = 0.401 (p>0.05) which means that age has no effect on blood pressure, smoking habits (p= 0.693) which means that smoking has no effect on blood pressure and years of service (p=0,590) which means that years of service do not affect the blood pressure of workers. After the workers were treated by wearing ear protective equipment their blood pressure decreased, thus there was a difference in the blood pressure of the workers before and after treatment. But on the characteristics of the workforce there is no effect on the increase in blood pressure. Suggestions that can be given to the industry are socialization about the application of proper use of ear protective equipment and providing ear protection equipment (earmuffs) in the workplace. Keywords: Noise, Ear Protection, Blood Pressure